Academic adaptation of Chinese postgraduate students in Malaysia - Shanshan Bi,; Abdul Latiff Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In recent years, there has been a notable rise in the number of Chinese applicants seeking admission to Malaysian tertiary education institutions, particularly for postgraduate programmes. This trend can be attributed to the favourable policies implemented by the Malaysian government. For Chinese students themselves, the prior task of studying abroad is to achieve their educational goals, which is challenging for them to study in an unfamiliar educational context. This study aims to explore Chinese postgraduate students’ academic adaptation to Malaysian research-oriented universities that provide qualified postgraduate programmes. Using qualitative methods, the study conducted semi-structured interviews with 15 Chinese postgraduate students studying in five Malaysian public universities. Thematic analysis was adopted to analyse the data collected. The study’s findings unveiled the various factors affecting Chinese postgraduate students’ academic adaptation throughout their postgraduate tenure, encompassing language ability, supervisor-supervisee relationship, pedagogic differences, academic support and emotional support. In addition, the study also highlighted the strategies that Chinese postgraduate students employed to embrace these challenges. The implications of the findings are expected to help Chinese postgraduate students develop effective strategies and programs to facilitate their academic adaptation in Malaysia. Further to this, these findings can offer recommendations to higher education institutions on how to collaborate effectively with Chinese students.